KERAGAMAN DAN ESTIMASI SIMPANAN KARBON PADA TEGAKAN HUTAN PANTAI UTARA CAGAR ALAM PULAU SEMPU JAWA TIMUR - Setyawan Agung Danarto; Ilham Kurnia Abiwijaya; R. Hendrian (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2018)
Abstract. Research on stand diversity and carbon stock in north coastal forest of Sempu Island Nature Reserve was conducted in May 2015. The study areas were focused on the coastal forest vegetation of Teluk Semut, Wedhen Cilik Beach, Caluk Ilang Beach, and Semenanjung Beach. The methods used for data collection were standard vegetation analysis with purposive sampling of 20 × 20 m2 plots along the exploration track by considering the representation of vegetation condition. A total of 51 tree species were recorded (belonging to 40 generas and 26 families) within the study area. Two threatened tree species found, according to IUCN Red List, were Myristica teysmannii Miq. (status: Endangered) dan Sindora javanica (Koord. & Valeton) Backer (status: Vulnerable). Stand diversity in Sempu Island coastal forest was high. Stand with diameter > 20 cm had high contributor in Sempu Island coastal forest. Maranthes corymbosa was higher contributor for carbon stoage in Sempu Island coastal forest. Keywords: Sempu Island Nature Reserve, stand diversity, carbon stock, north coastal forest